The Bull or Bear Characterization of Bitcoin Market Conditions - Emmanuel Ikechukwu Mba; Ifeoma Christy Mba; Winnie Ogonna Arazu; Tobias Ejiofor Ugah; Chinasa Ebere Urama (International Journal of Supply Chain Management, 2021)
The bear and bull market conditions have attracted a lot of attention as economic phenomena, thus characterizing the bitcoin markets as bullish or otherwise bearish goes a long way in describing the behaviour of the market. However, this paper will use the regime switching method to identify the turning points of the Bitcoin market conditions, predict the bull and bear Bitcoin market conditions and also emphasize the properties of the bear and bull market conditions that would aid investors in making the right investment decisions.